THE ADDITION OF MORINGA FLOUR IN THE DIET INCREASED THE WEIGHT OF THE WHITE RAT LIVER - Botha, Maria Natalia Dhiu; Setiasih, Ni Luh Eka; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2018)
This study aims to determine the addition of moringa flour (Moringa oleifera) in the feed to the weight of the liver of white rats (Rattus norvegicus). Moringa leaf flour was administered orally in 20 rats divided into 5 treatment groups with 0%, 2.5%, 5.0%, 10% and 20% concentration respectively with five replicates for one month. The white mouse was dissected and weighed heavily.  This study used a Completely Randomized Design (RAL). The data obtained were analyzed using ANOVA (analysis of variance), and continued by Duncan Multiple Range Test. The results obtained were the addition of 20 ml of Moringa oleifera flour in the diet to increase the liver weight of white rat ( Rattus norvegicus ), while the addition of maize flour 10%, 5% and 2.5% did not affect to the white rat’s ( Rattus norvegicus ) liver weight.